Effect of monomer distribution on the efficiency of poly(styrene-co-maleic acid) lipid particle (SMALP) formation - Cunningham, Randy Duwayne (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2020.